2003
DOI: 10.1021/bi035561s
|View full text |Cite
|
Sign up to set email alerts
|

Specific Non-Native Hydrophobic Interactions in a Hidden Folding Intermediate:  Implications for Protein Folding

Abstract: Structures of intermediates and transition states in protein folding are usually characterized by amide hydrogen exchange and protein engineering methods and interpreted on the basis of the assumption that they have native-like conformations. We were able to stabilize and determine the high-resolution structure of a partially unfolded intermediate that exists after the rate-limiting step of a four-helix bundle protein, Rd-apocyt b(562), by multidimensional NMR methods. The intermediate has partial native-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
107
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(112 citation statements)
references
References 55 publications
5
107
0
Order By: Relevance
“…All of the results consistently show that the core helices II+III fold first followed by helix IV and then helix I. Bai and co-workers then created different constructs with the native state mutationally destabilized so that other states normally at higher free energy became dominantly populated, and solved their solution structures by NMR. Well-folded structures were found, nearly identical to the first and second PUFs found by NHX Feng et al 2003aFeng et al , b, 2005a. The helices maintain their near-native main-chain conformation but the newly exposed apolar side-chains energy minimize by significant non-native repacking.…”
Section: Apocytochrome B 562 (Apocyt B 562 )supporting
confidence: 79%
See 1 more Smart Citation
“…All of the results consistently show that the core helices II+III fold first followed by helix IV and then helix I. Bai and co-workers then created different constructs with the native state mutationally destabilized so that other states normally at higher free energy became dominantly populated, and solved their solution structures by NMR. Well-folded structures were found, nearly identical to the first and second PUFs found by NHX Feng et al 2003aFeng et al , b, 2005a. The helices maintain their near-native main-chain conformation but the newly exposed apolar side-chains energy minimize by significant non-native repacking.…”
Section: Apocytochrome B 562 (Apocyt B 562 )supporting
confidence: 79%
“…Accordingly, one often finds evidence in partially folded intermediates for non-native interactions in addition to strikingly native-like conformation (Radford et al 1992;Capaldi et al 2002;Krishna et al 2004b;Feng et al 2005a;Bollen et al 2006;Neudecker et al 2007). Most noteworthy, Bai and colleagues solved the NMR solution structures of two apoCyt b 562 PUFs (Feng et al 2003a(Feng et al , 2005a. They are largely identical to the two partly unfolded forms found previously by NHX (Fuentes & Wand, 1998a, b;Chu et al 2002;Takei et al 2002) but distinct non-native interactions are also present, evidently because they help to energy minimize the PUFs.…”
Section: Foldon Structurementioning
confidence: 52%
“…For the assignment of main chain ( 1 H N , 15 N, 13 C α ) and 13 15 N-HSQC spectra were collected at 0.5 pH unit intervals, and mapped to known assignments to follow the movement of crosspeaks as pH was increased. Overlapping crosspeaks were separated by additional CBCA (CO)NH and HNCACB experiments coupled with H to D exchange.…”
Section: Nmr Assignmentmentioning
confidence: 99%
“…The C-terminal domain is set from residue 13 to residue 75 based on a computer program CONTACTS, which evaluates the atomic coordinates and identifies all potential van der Waals and hydrogen bonding interactions between any two defined sets of residues. It is found that the C-terminal domain (a start methionine followed by residues 75-164, a Ser(Gly) 4 Ala linker, and residues 1-12) can only fold into a marginally stable structure. This is consistent with our protein engineering results that the nine residues from Leu66 to Ala74 are important for the stability of the Cterminal domain.…”
Section: Structure and Backbone Dynamics Of The Hidden Intermediatementioning
confidence: 99%
“…5(a)), suggesting that they exchange through global unfolding. We fitted the ΔG HX s of Ala97 in the region from 0.3 M to 0.8 M GdmCl to a linear equation: (4) where ΔG NU D2O represents the global unfolding free energy extrapolated to 0 M denaturant and m NU represents the denaturant dependence of the unfolding free energy (dotted line in Fig. 5).…”
Section: Native-state Hydrogen Exchangementioning
confidence: 99%